The APOE∗3-Leiden Heterozygous Glucokinase Knockout Mouse as Novel Translational Disease Model for Type 2 Diabetes, Dyslipidemia, and Diabetic Atherosclerosis - Marianne G. Pouwer; Suvi E. Heinonen; Margareta Behrendt; Anne-Christine Andréasson; Arianne van Koppen; Aswin L. Menke; Elsbet J. Pieterman; Anita M. van den Hoek; J. Wouter Jukema; Brendan Leighton; Ann-Cathrine Jönsson-Rylander; Hans M. G. Princen (Journal of Diabetes Research)
Background. There is a lack of predictive preclinical animal models combining atherosclerosis and type 2 diabetes. APOE∗3-Leiden (E3L) mice are a well-established model for diet-induced hyperlipidemia and atherosclerosis, and glucokinase+/− (GK+/−) mice are a translatable disease model for glucose control in type 2 diabetes. The respective mice respond similarly to lipid-lowering and antidiabetic drugs as humans. The objective of this study was to evaluate/characterize the APOE∗3-Leiden.glucokinase+/− (E3L.GK+/−) mouse as a novel disease model to study the metabolic syndrome and diabetic complications. Methods. Female E3L.GK+/−, E3L, and GK+/− mice were fed fat- and cholesterol-containing diets for 37 weeks, and plasma parameters were measured throughout. Development of diabetic macro- and microvascular complications was evaluated. Results. Cholesterol and triglyceride levels were significantly elevated in E3L and E3L.GK+/− mice compared to GK+/− mice, whereas fasting glucose was significantly increased in E3L.GK+/− and GK+/− mice compared to E3L. Atherosclerotic lesion size was increased 2.2-fold in E3L.GK+/− mice as compared to E3L (p=0.037), which was predicted by glucose exposure (R2=0.636, p=0.001). E3L and E3L.GK+/− mice developed NASH with severe inflammation and fibrosis which, however, was not altered by introduction of the defective GK phenotype, whereas mild kidney pathology with tubular vacuolization was present in all three phenotypes. Conclusions. We conclude that the E3L.GK+/− mouse is a promising novel diet-inducible disease model for investigation of the etiology and evaluation of drug treatment on diabetic atherosclerosis.